ACQUISITION OF THE CONCEPT OF TIME IN CHILDREN (World Bulletin of Social Sciences, 2025)
This article analyzes the process of developing the concept of time in children from a psycholinguistic perspective. Additionally, it highlights the study of the concept of time within the framework of world linguistics and Uzbek linguistics, as well as the features of expressing time units through linguistic means. The study utilizes the results of psycholinguistic experiments, explains the stages of formation of basic time units in children, such as "yesterdaytoday-tomorrow," and puts forward proposals for mastering the concept of time in the educational process.